Radiographic differences in the concomitant deformities in two types of medial ankle osteoarthritis - Choi, Wooyoung (PLoS One, 2021)
OBJECTIVES: Motion preserving surgeries could be unsuccessful because of underestimation of deformities of the foot and knee in ankle osteoarthritis. This study aimed to investigate the concomitant deformities in medial ankle osteoarthritis and the difference between the two types, varus angulation and medial translation. METHODS: A retrospective study was conducted using medical records and radiographic data. Patients with medial ankle osteoarthritis that underwent weight-bearing X ray imaging and radiographic measurements including tibial plafond inclination (TPI), tibiotalar tilt angle (TT), lateral talo-first metatarsal angle, naviculo-cuboid overlap, and mechanical tibiofemoral angle (mTFA) were studied. The patients were categorized into two groups, the varus angulation group (TT ≥4°) and medial translation group (TT <4°). The radiographic measurements were compared between the two groups. RESULTS: A total of 102 patients (male = 44; female = 58) were included; the mean age was 64.9 years (SD 8.3 years). The varus rotation group (N = 66) showed a significantly smaller lateral talo-first metatarsal angle (p<0.001), naviculo-cuboid overlap (p<0.001), and mTFA (p = 0.019) compared to the medial displacement group (N = 36). The TT showed a significant correlation with lateral talo-first metatarsal angle (r = -0.520, p<0.001), naviculo-cuboid overlap (r = -0.501, p<0.001), and mTFA (r = -0.243, p = 0.014). Lateral talo-first metatarsal angle was found to be the significant factor (p = 0.018) discriminating varus angulation and medial translation types in the binary logistic analysis. CONCLUSIONS: Varus angulation of the ankle was correlated with knee alignment and foot deformity. Radiographic indices were different between the varus angulation and medial translation groups. The role of concomitant deformities needs to be further investigated in terms of a causal relationship. Surgeons need to pay attention to concomitant deformities in the treatment of medial ankle osteoarthritis.